KNOWLEDGE AND AWARENESS LEVELS OF PREGNANT WOMEN AGED 15-49 YEARS REGARDING THE IMPORTANCE OF TIMELY ANTENATAL CARE AND ITS IMPACT ON MATERNAL AND FOETAL HEALTH AT NSANGI HEALTH CENTRE III. A CROSS-SECTIONAL STUDY. - Namubiru, Angel; Okwany, Jimmy; semuwemba, Francis; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2024)
Background The knowledge and awareness levels of pregnant women regarding the importance of timely antenatal care enrolment can have a significant impact on their maternal and foetal health. The study aims to assess the knowledge and awareness levels of pregnant women aged 15-49 years regarding the importance of timely antenatal care and its impact on maternal and fetal health at Nsangi Health Center III. Methodology The study employed a cross-sectional design, utilizing quantitative data collection methods. The study targeted patients in the ANC department. A sample size of 80 respondents was determined using Cochran’s formula. The study utilized a simple random sampling technique to select respondents. Data analysis was performed using Microsoft Office Excel 2021 and SPSS version 23. Results 85.0% of the respondents were aware of the term "Antenatal Care," 56.3% were aware that it should begin in the first trimester, 40.0% understood that it should be monthly, 22.5% every two months, 25.0% trimester-wise, and 12.5% based on personal preference. 51.3% recognized it as a means to monitor the health and growth of the baby, 32.5% acknowledged its role in detecting and managing pregnancy-related complications and 1.3%. Among the 80 respondents, 21 (26.3%) recognized the potential harm to both mother and baby due to undiagnosed maternal health conditions. Additionally, 33 (41.3%) understood. Conclusion There was a high level of awareness about antenatal care and its importance among the study population with respondents well-informed about the ideal timing for starting antenatal care, with an emphasis on early care in the first trimester. Recommendation Pregnant women should actively seek antenatal care as early as possible, ideally in the first trimester.